Triglyceride-Glucose Index as Predictor for Hypertension, CHD and STROKE Risk among Non-Diabetic Patients: A NHANES Cross-Sectional Study 2001-2020 - Bisher Sawaf; Sarya Swed; Hidar Alibrahim; Haidara Bohsas; Tirth Dave; Mohamad Nour Nasif; Wael Hafez; Fatema Ali Asgar Tashrifwala; Yazan Khair Eldien Jabban; Safwan Al-Rassas; Heba haj Saleh; Abdul Rehman Zia Zaidi; et al. (Springer, 2024)
Abstract Background Cardiovascular disease (CVD) is a leading cause of global mortality. Early intervention and prevention of CVD depend on accurately predicting the risk of CVD. This study aimed to investigate the association between the TyG index and the risk of coronary heart disease (CHD), congestive heart failure (CHF), heart attack (HA), stroke, and hypertension (HTN) among patients without diabetes in the United States. Methods In this retrospective, cross-sectional study, we used data from the National Health and Nutrition Examination Survey (NHANES) from 2001 to 2020. We conducted several regression analysis models and calculated the sensitivity and specificity of (TyG) index for predicting the onset of CHD, CHF, HA, stroke, and HTN. Results A total of 10,937 individuals without diabetes participated in our study. Individuals with a TyG index greater than 8.96 displayed significant increasing in various parameters, including BMI, systolic/diastolic blood pressure, total cholesterol, LDL, and Apo-B levels (p < 0.001). Almost all regression models ensured that a higher TyGI value was associated with higher odds of having CHD, CHF, HA, stroke, and HTN, which patients with a TyGI value higher than 8.96 have odds ratios of 2.24-5.58 for CHD, 1.68-4.42 for stroke, 2.45-3.77 for HA and 1.75-3.93 for HTN comparing than patients with a TyGI value lower than 8.11 (p-value < 0.05).We evaluated the predictive value of the TyG index for each endpoint, obtaining the following area under the curve (AUC) values: 54.75% for CHF (95% CI: 0.542-0.614), 52.32% for stroke (95% CI: 0.529-0.584), 55.67% for HA (95% CI: 0.595-0.646), 55.59% for HTN (95% CI: 0.574-0.597), and 50.31% for CHD (95% CI: 0.592-0.646). Conclusion The TyG index showed a strong correlation with cardiovascular risk factors in individuals without diabetes, however it was a poor predictor of almost studied cardiovascular diseases.